THE ROLE OF PHRASEOLOGICAL UNITS IN UZBEK AND ENGLISH DIALOGUES (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
Phraseological units (PUs) play a crucial role in communication by enhancing expressiveness, conveying emotions, andembedding cultural nuances in dialogues. This study examines the role of PUs in Uzbek and English dialogues, focusing on theirstructure, function, and cultural significance. Using a comparative analysis of authentic conversational examples, the researchhighlights similarities and differences in the usage of phraseological units in both languages. Findings suggest that while Uzbekand English employ PUs for emphasis, humor, and metaphorical expression, their cultural and historical contexts significantlyshape their meaning and application.